1973
DOI: 10.1002/pssb.2220560229
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Chemical Shift of Nuclear Magnetic Resonance in Single Crystals of Tellurium and Selenium. I. Experimental Studies

Abstract: Nuclear magnetic resonances of 12Te and 7% have been observed in single crystals of tellurium and selenium, respectively. They consist of three resonance lines, each of which shows a highly anisotropic chemical shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Solid-state NMR investigations of elemental selenium have demonstrated the sensitivity of 77 Se chemical shifts to minor changes in the local environment since the initial investigation of a single crystal of trigonal selenium at 77 K (Table 2) [84]. This study indicated that the most shielded principal component lies nearly parallel to the direction of the helices [84][85][86]. Subsequent variable temperature experiments up to 480 K have demonstrated a general decrease in selenium shielding with increasing temperature for crystalline selenium, see Table 2 [87][88][89].…”
Section: Seleniummentioning
confidence: 91%
“…Solid-state NMR investigations of elemental selenium have demonstrated the sensitivity of 77 Se chemical shifts to minor changes in the local environment since the initial investigation of a single crystal of trigonal selenium at 77 K (Table 2) [84]. This study indicated that the most shielded principal component lies nearly parallel to the direction of the helices [84][85][86]. Subsequent variable temperature experiments up to 480 K have demonstrated a general decrease in selenium shielding with increasing temperature for crystalline selenium, see Table 2 [87][88][89].…”
Section: Seleniummentioning
confidence: 91%
“…The overall line width of the Ru/Se sample is greater than that of Ru x Se y , because to the larger heterogeneity of the Ru surface sites in the catalyst prepared from commercial Ru nanoparticles. In contrast, the 77 Se NMR spectrum of elemental Se is far narrower, Figure a, with three partially resolved peaks, corresponding to the three nonequivalent Se sites seen crystallographically . The center of mass of the elemental Se NMR spectrum occurs at 857 ppm, so there is a ∼813 ppm downfield shift for Se atoms when bonded to Ru.…”
mentioning
confidence: 96%
“…For selenium the estimated value of the diamagnetic term in (1) is nearly the same as that for tellurium, whereas the observed magnitude of oA is about 5 x 10-4 [3]. Since the isotropic part of the chemical shift is also included in the above estimation, the contribution of the diamagnetic term to IS, may be less then the above estimation.…”
Section: Knight Shift and Chemical Shiftmentioning
confidence: 64%
“…The observed magnitude of (TA is as large as 1.7 x in tellurium [3], and thus the diamagnetic term does not seem to contribute to OA for tellurium.…”
Section: Knight Shift and Chemical Shiftmentioning
confidence: 86%
See 1 more Smart Citation